2017
DOI: 10.1097/qmh.0000000000000129
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Barriers: A Study of Quality Improvement Work Among Nurses and Physicians

Abstract: This article studies interprofessional barriers between nurses and physicians in the context of quality improvement work. A total of 17 nurses and 10 physicians were interviewed at 2 hospitals in Sweden. The study uncovered a number of barriers relating to both the relative status of each group and their defined areas of responsibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 34 publications
(33 reference statements)
3
17
1
Order By: Relevance
“…This finding was somewhat surprising and contradicts several other studies, which show that doctors often do not value the independent opinions of nurses and consider nurses responsible only for carrying out doctors' orders (Reeves et al, 2009;Tan et al, 2017;Tang et al, 2013). There are many indications that this culture is gradually changing and that the role of the nurse is developing toward more independence (Currie et al, 2010;Eriksson & Müllern, 2017;Niezen & Mathijssen, 2014).…”
Section: Discussioncontrasting
confidence: 56%
“…This finding was somewhat surprising and contradicts several other studies, which show that doctors often do not value the independent opinions of nurses and consider nurses responsible only for carrying out doctors' orders (Reeves et al, 2009;Tan et al, 2017;Tang et al, 2013). There are many indications that this culture is gradually changing and that the role of the nurse is developing toward more independence (Currie et al, 2010;Eriksson & Müllern, 2017;Niezen & Mathijssen, 2014).…”
Section: Discussioncontrasting
confidence: 56%
“…Although not the original intent of this project, findings from the articles reviewed support nurse engagement in QI as a critical component to quality and safety .22,24,27 However, what supports engagement at work and how it equates to engagement must be further explored .27,29 influential to QI engagement, including building a culture of safety, 23,29 QI collaboratives, 19 and interprofessional relationships between nurses and physicians. 28 Further evaluation of the effectiveness of such strategies in improving nurse engagement is needed. Mentors/champions of QI were found to be a facilitator, with frontline nurses looking to nurses with expertise in QI to be their QI mentors.…”
Section: Discussionmentioning
confidence: 99%
“…The study findings highlight the need to narrow the gap in perceptions and to encourage teamwork. Previous studies reported that physicians and nurses working together as a team was associated with better health outcomes and good quality of care (Eriksson & Müllern, 2017; Niezen & Mathijssen, 2014; Price et al, 2013). Additional explanations for the differences in perception may be gender related.…”
Section: Discussionmentioning
confidence: 99%